KEY CHALLENGES IN THE FIELD OF PROCESS CONTROL WHEN USING RENEWABLE ENERGY SOURCES - Давидов, Валентин; Бєлов, Віктор (SWorldJournal, 2023)
This article explores and discusses key issues in the field of process control in the use of renewable energy sources. Issues such as uncertainty in energy production, integration of different sources, effective management of energy storage, and the crea